Comparison of Spinal and General Anaesthesia in Caesarean Section and Its Effect on Mother and Neonate - Gurbani, Dr. Ravi; Vachhani, Dr. Rashim (International Journal of Innovative Research in Medical Science, 2018)
Introduction Now a day the choice of obstetric anaesthesia has been influenced by patient and physician preferences and the frequency of caesarean section births continues to increase steadily worldwide.[1] Even though it is safe over the years and due to advancement but it is still associated with high rates of maternal and perinatal mortality and morbidity.[2] Spinal anaesthesia is a mainstay in Caesarean Section. It avoids a general anaesthetic with risks of failed intubation in case of anatomical abnormalities in mother, and risks of ventilation in respiratory diseases. It is easy to administer, improved needles reducing the post punctural headache and also the faster onset time is in the favour of spinal anaesthesia. Also the mother is conscious and partner can be present at the time of birth of the baby. General anaesthesia has superior control over ventilation, lower incidence of hypotension as seen with spinal anaesthesia, speed of induction, and there is lack of awareness of the perioperative period is preferred in emergency situations and in selected and elective procedures,[3] but complications such as maternal aspiration syndrome may occur during general anaesthesia and thus contribute towards maternal mortality.[4] Use of anaesthetic drugs that cross the placental barrier can nevertheless produce neonatal depression.[5] Thus rates of caesarean section using spinal anaesthesia have been increasing and spinal anaesthesia is becoming the preferred anaesthetic technique for avoiding maternal and fetal complications.[6,7] Some anaesthetists prefers spinal anaesthesia under elective conditions. But due to sympathetic blockade of spinal anaesthesia-related hypotension may affect neonatal short-term outcomes by impairing uteroplacental perfusion[8] also cerebrospinal fluid (CSF) leakage following lumbar puncture may cause headache, nausea and vomiting.[9] In some occasion conversion of spinal to general anaesthesia has been seen due to insufficiency of regional blockade. Now a days the choice of anaesthesia depends on the mother's request, obstetric reasons and the anaesthesiologist’s experience level.